2015
DOI: 10.1002/wsbm.1289
|View full text |Cite
|
Sign up to set email alerts
|

Systems biology of polycystic kidney disease: a critical review

Abstract: The proliferation and diminishing costs of ‘omics’ approaches have finally opened the doors for small and medium laboratories to enter the ‘systems biology era’. This is a welcome evolution that requires a new framework to design, interpret and validate studies. Here we highlight some of the challenges, contributions, and prospects of the“cyst-ems biology” of polycystic kidney disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 60 publications
1
13
0
Order By: Relevance
“…This comparison will be the subject of a future communication. Other evaluations of gene expression data have relied on murine cell lines or RNA isolated from newly formed cysts from conditional knockout models, and results from these studies identify similar themes for aberrant signaling such as immune defense, cell structure and motility, cellular proliferation, apoptosis, and metabolic control [5962]. These are GSEA findings that are also observed in our study suggesting that a subset of findings observed in our cell lines are generalizable.…”
Section: Discussionsupporting
confidence: 75%
“…This comparison will be the subject of a future communication. Other evaluations of gene expression data have relied on murine cell lines or RNA isolated from newly formed cysts from conditional knockout models, and results from these studies identify similar themes for aberrant signaling such as immune defense, cell structure and motility, cellular proliferation, apoptosis, and metabolic control [5962]. These are GSEA findings that are also observed in our study suggesting that a subset of findings observed in our cell lines are generalizable.…”
Section: Discussionsupporting
confidence: 75%
“…Second, it is necessary to exploit novel molecular genetic techniques to pinpoint the molecular mechanisms known to cause common kidney diseases (7,8). This is because kidney pathologies are lumped together by their temporal patterns (acute or chronic) or by their target structure (glomerular vs tubular), which obscures the underlying kidney biology and prevents targeted precision medicine.…”
mentioning
confidence: 99%
“…E‐F). Thus, gender might influence cystogenesis in the ADPKD kidney, with female gender being a protective factor both in the animal model and in ADPKD patients .…”
Section: Resultsmentioning
confidence: 99%